176-81: Implanted defibrillators in trouble: initial device misclassification leads to correct diagnosis. (10th June 2016) - Helge, Knopp; Ebert, Micaela; Seewöster, Tim; Hilbert, Sebastian; Lucas, Johannes; Döring, Michael; Richter, Sergio; Hindricks, Gerhard; Arya, Arash; Müssigbrodt, Andreas
Abstract: Aims: Supraventricular tachycardia, mistakenly diagnosed as VT may lead to inappropriate ICD therapy. Inappropriate ICD therapy associates with increased morbidity and mortality. A reduction of inappropriate therapy is therefore desired. Methods: We present three different cases oft SVT with consecutive atrio-ventricular activiation that beautifully illustrate the diagnostic possibilities of stored electrograms. Results: Initial differential diagnoses in all three patients included ventricular tachycardia, focal atrial tachycardia, atrio-ventricular reentry tachycardia and atrio-ventricular nodal reentry tachycardia. The first case was diagnosed as atrio-ventricular nodal reentry tachycardia. In the second case orthodromic atrio-ventricular reentry tachycardia by a conceald left accessory pathway was revealed. Ectopic atrial tachycardia was the reason for inappropriate therapy in the third patient. Conclusion: Thorough analysis of stored electrograms yielded correct diagnosis in all cases, which subsequently was confirmed by electrophysiological study.